El empleo y la recaudación tributaria del departamento de Loreto periodo 2018 – 2022 - Chero Gratelli, Luz Marina (2024)
Employment is closely linked to the development of the economy. If production grows, then the economy grows, employment increases and tax collection increases. But employment must be formalized, since the informal sector is an obstacle to the healthy growth of the economy. The objective of this research is to determine the relationship between employment and tax collection in the department of Loreto, in the period 2018 - 2022. That is why this research is carried out, classified as Quantitative based on its nature, and Correlational, taking into account The level of explanation takes into account, being structured under a Non-Experimental design. The conclusion is reached that employment is directly associated with the level of tax collection in Loreto, during the five-year period 2018 - 2022, because the Correlation Coefficient is r = 0.756258687; but it does not determine its behavior since the Coefficient of Determination is R2 = 0.571927202. Tax revenues are basically explained by the collection of Income Tax, since it generates 54.63% of them. On the other hand, tax collection maintained a positive behavior throughout the period, growing in general terms at an average annual rate of 15.20%. The employment analysis shows that the employed population has been working mostly in the Agriculture and Fishing branch of economic activity (30.51%).